Implementation of Inquiry Learning Models in Improving Student Collaboration and Learning Results - Ardyansyah, Darmawan; Zakiyyah, Zakiyyah; Taufik, Leo Muhammad (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the implementation of the inquiry learning model in improving collaboration and student learning outcomes. This study uses a Quantitative method, in this study a quasi-experiment research type is used to find out the comparison before and after the action using the Inquiry learning model. The type of design in the quasi-experiment used is the pretest-posttest nonequivalent control group design. The population in this study is grade VIII student MTS Nurul Huda Beringin. The sample used was 80 students from classes VIII A and VIII B MTS Nurul Huda Beringin. The research instrument uses a test sheet consisting of 6 questions and an observation sheet. Data management techniques use descriptive statistic tests, normality tests, hypothesis tests, and N-Gain tests. The results of the study show that the implementation of the inquiry learning model in improving collaboration and student learning outcomes with the theme of the structure of the earth layer applies learning with 2 class groups, namely the experimental class and the control class. The results of the study show that the application of the inquiry learning model is able to increase student collaboration in group learning activities, as shown by the collaboration observation score, which is mostly in the good to very good category. In addition, student learning outcomes in the experimental class experienced a significant increase compared to the control class. Thus, the implementation of the inquiry learning model is effective in improving collaboration skills as well as student learning outcomes on the structure of the earth's layer.